The politics of local government stabilization funds - Snow, Douglas; Haughton, Jonathan; Gianakis, Gerasimos A. (2015)
The adoption, maintenance, and prudent use of budgetary stabilization funds are fundamental financial management precepts, yet the variables that influence the size of these funds are poorly understood. This article contributes to the stabilization fund literature by examining the extent to which variation in stabilization fund balances across municipalities and over time can be explained by a community's political culture and financial management capacity. The balanced panel research design includes archival data for 239 Massachusetts municipalities for each of 18 fiscal years. Stabilization fund balances are lower in communities with either an anti-tax or a pro-spending political culture. Stabilization fund balances are higher in communities that have the financial management capacity to accumulate budget surpluses that can be made available for appropriation to stabilization funds. Communities with the open town meeting form of government also have higher stabilization fund balances. - Reproduced.
Keywords: Local finance; Local government